PENGARUH KOMPETENSI TERHADAP KINERJA PEGAWAI DAN MOTIVASI SEBAGAI VARIABEL INTERVENING PADA KANTOR UPTD PENDAPATAN WILAYAH I PALU - Gunawan, Gunawan (Katalogis, 2015)
UPTD (regional technics revenue unit) Palu is one of office which provide service to community. To provide best service, this office needs personnel that have best performance and motivation. In line eith this argument, this research aims to know measure and analyze direct effect of competency and indirect effect of competency through motivation on performance. This research employs path analysis using regression equation approach. The results shows that competency performs positive and significant effect on motivation with regression coefficient 0,619. Motivation performs positive and significant effect directly on performance, therefore it can be concluded that motivation is an intervening variable. This is indicated by regression coefficient 0,294. Competency performs positive and significant effect directly on performance with coefficient regression 0,416. In addition, competency performs positive and significant effect directly on performance through motivation at UPTD Regional Revenue I Palu which is indicated by effect 0,182.